2017
DOI: 10.21859/cej-030915
|View full text |Cite
|
Sign up to set email alerts
|

Flood Analysis in Karkheh River Basin using Stochastic Model

Abstract: This study analyzed the annual streamflow of Karkheh River in Karkheh river basin in the west of Iran for flood forecasting using stochastic models. For this purpose, we collected annual stremflow (peak and maximum discharge) during the period from 1958 to 2015 in Jelogir Majin hydrometric station (upstream of Karkheh dam reservoir). A time series model (stochastic model or ARIMA) has three stages consists of: model identification, parameter estimation and diagnostic check. Model identification was done by vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
(4 reference statements)
0
6
0
1
Order By: Relevance
“…First, the quantitative research method was used to supplement the research breadth [ 68 ], and then the qualitative research method was used to increase the depth of the research [ 69 ], which can atone for the shortcomings of research method or theory [ 68 ]. Therefore, for this study, first, the relevant literature was referred to [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ], the questionnaire tool was edited, and then three experts were invited to check the content validity. After the amendment, 100 questionnaires were collected in June 2021, analyzed using SPSS 26.0 statistical software, and confirmed as the official questionnaire tool.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the quantitative research method was used to supplement the research breadth [ 68 ], and then the qualitative research method was used to increase the depth of the research [ 69 ], which can atone for the shortcomings of research method or theory [ 68 ]. Therefore, for this study, first, the relevant literature was referred to [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ], the questionnaire tool was edited, and then three experts were invited to check the content validity. After the amendment, 100 questionnaires were collected in June 2021, analyzed using SPSS 26.0 statistical software, and confirmed as the official questionnaire tool.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, recent studies on rivers and water conservancy projects have been carried out based on river velocity, water volume, and water quality to analyze flood and ecological impacts [ 40 , 44 , 45 , 46 , 47 ]. In response to climate change, some researchers have begun to explore the utilization of water resources in reservoirs, rivers, and cities [ 30 ] and the impact of water conservancy projects on urban or rural development [ 42 , 48 ] and people’s lives [ 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…A stochastic model has been developed in order to analyze the annual stream flow of Karkheh River in Iran for flood forecasting. The obtained results indicated that the ARIMA model was adequate for flood analysis in Karkheh River and for the prediction of the series in a short time in the future [3]. Similarly, a stochastic model has been established for reducing economic floods risk in Yewa sub-basin, by adjusting maximum annual momentous discharge into four probability distributions.…”
Section: Introductionmentioning
confidence: 88%
“…The dimensional flood models are widely adopted by researchers due to its simplicity compared to all flood models. Machekposhti et al (2017) [16] studied annual flowstream with two variables peak and maximum discharge for upstream Karkheh dam reservoir by using time series model. This can be achieved by the help of the Partial and Autocorrelation Function (ACF and PACF).…”
Section: Introductionmentioning
confidence: 99%